Neurotrophin signalling in the human nervous system - Ateaque, Sarah; Merkouris, Spyros; Barde, Yves-Alain (Frontiers in Molecular Neuroscience, 2023)
This review focuses on neurotrophins and their tyrosine kinase receptors, with an emphasis on their relevance to the function and dysfunction in the human nervous system. It also deals with measurements of BDNF levels and highlights recent findings from our laboratory on TrkB and TrkC signalling in human neurons. These include ligand selectivity and Trk activation by neurotrophins and non-neurotrophin ligands. The ligand-induced down-regulation and re-activation of Trk receptors is also discussed.